Combined morphological and molecular approaches to the clinical diagnosis of Necator americanus infection: a case report - Xianshu Liu; Ailian Sun; Xingxing Zheng; Meng Xia; Yan Liu; Shuaiqin Huang; Xiang Wu (Journal of Medical Case Reports, 2025)
Abstract Background Hookworm infection remains of considerable importance to public health. However, because critical cases caused by hookworm infection are rarely observed in China, accurate and prompt diagnoses are difficult to achieve in clinical practice. In this study, we describe how we combined morphological and molecular approaches to achieve the clinical diagnosis of hookworm infection. Case presentation A 75-year-old Chinese woman who presented with dizziness, poor appetite, poor sleep, and weakness in her limbs was diagnosed with chronic atrophic gastritis and was positive for Helicobacter pylori, iron deficiency anemia with a hemoglobin concentration of 35 g/L, and left atrial enlargement. However, after symptomatic treatment, the patient did not improve. Upper gastrointestinal endoscopy revealed the presence of live nematodes in the descending portion of the patient’s duodenum. Fecal examination via saturated brine flotation revealed hookworm eggs. Further verification via semi-nested reverse transcription-polymerase chain reaction assay confirmed provided confirmation that the hookworm species was Necator americanus. Albendazole was used for antihelminthic treatment. Through follow-up visits, we found that the antihelminthic treatment was successful and that her anemia was cured. Conclusion In this study, a combination of morphological and molecular approaches were used to make a definite diagnosis of severe iron deficiency anemia caused by Necator americanus infection in a patient. The results presented here provide suitable guidance for the clinical diagnosis of hookworm infection and a powerful tool for the identification of hookworms.